Trichocoptomania - Garofalo, L. (European Journal of Pediatric Dermatology, 2019)
We propose the name of trichocoptomania (from the Greek κοπτω = to bang) which has a similar meaning to other more frequent forms such as trichotillomania, trichoteiromania – from repeated scratching – (1) and to the exceptional trichodaganomania (2) – from bites – linked to a defective impulse control and to the search for pleasant sensations. In the adult these lesions, especially if provoked in secret, have a meaning of psychosis, while in the child, especially when implemented coram populo they have the meaning of a tic and thus minor importance. A similar finding can also be linked to sports such as break dance. More severe and dangerous, but rare in children, is the mania of ingesting the hair after having torn it, which causes the formation in the stomach of masses of partially digested hair (tricobenzoars). Another form of traumatic alopecia is tricotemnomania, usually performed with a scissors or razors by a parent.